Experimental investigation of combustion characteristics analysis and optimization during the turbocharging mode switching process of diesel engine with advanced turbocharging system. (25th March 2023) - Qiu, Hongjian; Leng, Ling; Song, Yanping; Cheng, Jianghua; Shi, Lei; Deng, Kangyao
Highlights: The turbocharging mode switching process of a TSST diesel engine is tested. The combustion characteristics of turbocharging mode switching are explored. The formation mechanism of cyclical combustion fluctuation is revealed. The combustion and performance fluctuation are optimized by valve regulation. Abstract: Multi-turbocharger system is one of the major enablers of modern diesel engine performance. To meet the boosting requirements under different operating conditions is the difficulty. The two-stage sequential turbocharging (TSST) system creates the flexibility to select the turbocharging mode so that the engine benefits from efficiency and power density. However, the critical issue at hand is the unstable running, or even worse, misfire, of the engine caused by the abrupt air path shifts during the turbocharging mode switching process. Therefore, the control of the switching process is an indispensable procedure to apply the TSST system. The previous studies mainly focused on turbocharging system parameters. The combustion characteristics during switching process have been underestimated. The combustion process is influenced by the fuel and charging variations during the transient process, and it is unique compared with the steady state. In this paper, the experiments of TSST system switching process were carried out to investigate the transient combustion characteristics, formation mechanism of its fluctuation, and optimal control. The experimental results indicate that the combustion present fluctuation during the direct switching process. The main features are the generation and extinction of premixed combustion, combining the degradation and recovery of mixing-controlled combustion. The cycle history of heat-release center (CA50) presents a 3-phase fluctuation of moving backward from 9.7°CA to11.2°CA, then forward to 6.2°CA, and finally backward to 10.7°CA. The boost pressure trough is the primary factor contributing to incomplete combustion. The lowest gross indicated efficiency of 33.9 % happened at the lowest air-fuel ratio cycle. Based on the corresponding results, the substantial improvement in combustion can be ensured by regulating the switch valves in air path. When the intake switch valve opens 0.9 s later than the exhaust switch valve, the system exhibits minimal parameter fluctuations and the quickest recovery capacity. The coefficients of variation for IMEPg and CA50 are 2.7 % and 4.6 %, respectively, guaranteeing at least 39.7 % fuel conversion efficiency and only 17 cycles to reach the steady state.